Revised biostratigraphic scheme for the Early Pleistocene of the UK based on arvicolids (Mammalia, Rodentia). (25th August 2014) - Mayhew, D.F.; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> This paper reviews the Early Pleistocene arvicolids from the UK, including new material, and updating the taxonomy and the stratigraphic interpretations. The biostratigraphic system for the Pliocene and Early Pleistocene proposed by Tesakov for southeast Europe is applied to the UK assemblages. Previous work which recognized three faunal groups is confirmed. The latest assemblages, from the 'Weybourne Crag' deposits (currently included in the Wroxham Crag Formation), fall within arvicolid biozone MNR1. The earlier arvicolids, from the Norwich Crag, fall within biozone MNR2, in two distinct levels. The later level, dating from the second half of biozone MNR2, includes the arvicolids from deposits exposed on the Suffolk coast near Southwold, including Easton Bavents. These underlie deposits previously assigned to the Baventian Stage. The earlier arvicolid assemblages date from the first part of biozone MNR2 (or just possibly the end of biozone MNR3) and come from Norwich Crag Formation deposits including the type Bramertonian (Bramerton, Norfolk), as well as deposits at and near the surface in the area of Sizewell (Suffolk). On the basis of palaeomagnetic calibration in southeast Europe, the three levels of the UK sequence are interpreted as corresponding to approximate absolute age limits of 2.1–2.25 Ma ('Weybourne Crag'), 2.25–2.35 Ma (the later Norwich Crag Formation) and 2.35–2.45 Ma (the earlier Norwich Crag Formation). The revised arvicolid biostratigraphy is considered to be valid for the North Sea Basin area, allowing correlation with deposits in the Netherlands, and a link to be made between continental and marine biostratigraphic schemes. Copyright © 2014 John Wiley & Sons, Ltd.